Recolonisation of a fish and invertebrate community in a wetland following a drought: the importance of deep water refugia. Issue 3 (3rd July 2021) - Stuart, Rose E.; Ingram, Travis; Closs, Gerard P.
ABSTRACT: Wetland restoration or re-establishment is a common conservation goal, and the ability of a wetland community to recover from events such as drought are key to its long-term success. At the mouth of the Waiau River in Southland, New Zealand, a series of wetland ponds have been created by diverting water from the river. A period of particularly low river flows resulted in the wetland drying out entirely, except for a few deep channels. A subsequent flood inundated the ponds, creating an opportunity to study recolonisation of the system. The deep channels provided an important refuge habitat for eels ( Anguilla spp.) during dry periods, with significantly higher numbers close to the channels immediately after refilling than at sites further away. Smaller fish ( Gobiomorphus and Galaxias spp.) took much longer to reappear in the ponds. The macroinvertebrate community showed no significant variation over the short term or up to a year post-refill, although individually snail and water bug taxa increased and microcrustaceans decreased in abundance. Daphnia and ostracods were observed soon after refilling and dominated the community. This study highlights the importance of spatial heterogeneity in constructed wetland systems, as this habitat variation likely increases the recovery rate after drying.